Handgrip Strength and Its Association With Hydration Status and Urinary Sodium-to-Potassium Ratio in Older Adults. (2nd April 2020) - Mendes, Joana; Padrão, Patrícia; Moreira, Pedro; Santos, Alejandro; Borges, Nuno; Afonso, Cláudia; Negrão, Rita; Amaral, Teresa F.
Abstract: Objective: Older adults present higher risk of functional disability detected by handgrip strength and an increased risk of poor health conditions, such as dehydration and low values of the sodium-to-potassium (Na/K) ratio. This study aimed to quantify the association of hydration status and Na/K ratio with handgrip strength, based on the urinary excretion of older adults. Methods: A cross-sectional study was conducted in 735 older adults ≥ 65 years old. Handgrip strength was measured with a Jamar Dynamometer and low values were defined according to body mass index and to sex-specific cutoff points. The hydration status was evaluated based on free water reserve. Sodium and potassium intake were evaluated after converting 24-hour urinary sodium and potassium excretion, respectively. A logistic regression model was used to estimate the probability of presenting low handgrip strength, according to risk of hypohydration and to quartiles of Na/K, stratified by sex and adjusted for potential confounders. Results: The adjusted odds ratio (OR) for presenting low handgrip strength was higher in women at risk of hypohydration, but this association was not found in men. Both women and men with the highest values of Na/K ratio presented higher adjusted OR for low handgrip strength (OR in women was 2.03; 95% confidence interval [CI]: 1.12–3.68, and in men was 2.19; 95% CI: 1.11–4.29). Conclusions: The risk of hypohydration was directly associated with low handgrip strength in older women. In older adults, higher values of urinary Na/K ratio were also directly associated with low handgrip strength.